DISCOURSE AND PSYCHOANALYSIS: TRANSLATING CONCEPTS INTO “FRAGMENTING” METHODOLOGY - Young, Lisa Saville; Frosh, Stephen (PINS-Psychology in Society, 2025)
There is a growing body of work that draws on psychoanalytic interpretive strategies to enrich our understanding of the psychological processes involved in an individual’s investment in particular discursive positions. This work champions the irreducibility of the social and the psychological, exploring the way in which the desires and wishes of the individual mediate the accessibility of social discourses. However, employing psychoanalysis as a framework for interpreting text necessarily means proceeding tentatively: rather than an individualising, theory-driven tool, the authors argue for its use in a way that “fragments” texts. Specifically, we demonstrate how psychoanalytic interpretation might be grounded in a fine-grained narrative analysis as well as in a reflexive interpretation of the research relationship, in order to seek ways to open out the text to produce various new discursive forms, rather than to “fix” their meaning.